A formação de professores para as relações étnico-raciais: uma análise das publicações acadêmicas de 2014 a 2022 - Azarias , Natan Reis (2023)
Law No. 10,639/2003 amended the Law on Guidelines and Bases of National Education (Law No. 9,394/1996) by inserting the mandatory teaching of Afro-Brazilian history and culture into the school curriculum, with among motivating aspects the need to combat racism and promoting the appreciation of Afro-Brazilian culture. Thus, Law No. 10,639/2003 seeks to promote inclusion and diversity, recognizing the importance of the contributions of Africans and Afro-descendants to the formation of Brazilian society. It is reasonable to expect that, 20 years after its promulgation, it will be possible to observe its effects on educational policy in relation to diversity because, during this period, debates on diversity in education have been stimulated in different areas of society, with the aim of combating prejudice and discrimination. Considering that it is not enough to introduce mandatory content without teacher training, there is a need to evaluate the necessary teacher training processes and reflect on the challenges to be faced and develop suggestions that can shed light on the debate on the effective implementation of the Law The objective of this work is to analyse academic production, in the form of scientific articles published in journals and related to teacher training for ethnic-racial relations, seeking to offer an overview of the main trends and contributions of literature on the topic, as well how to identify gaps in research and areas in need of further investigation. As a result, we present a literature review on the topic from 2014 to 2022 and compare this production with literature data reported for the period 2003 to 2013. Considering the database used, as well as the inclusion criteria defined in advance, we group the 41 academic publications that made up the analysis corpus in the Curricula and Programs categories; Affirmative Action and Educational Policies; Pedagogical Proposals and Practices; Identities; and Pedagogical Instruments, classes already present in the literature and which reflect the predominant themes in the discussion on the implementation of Law 10639/2003 in the first decade of its implementation. When comparing the frequencies of articles in each category in relation to the total number of articles, we found that, in the first decade of the Law's validity, the themes Curricula and Programs and Affirmative Actions and Educational Policies were predominant, while the second decade is marked by the predominance of themes Pedagogical Proposals and Practices and Identities, showing a change of focus in the debate on the topic. Furthermore, the evolution of academic production points to the consolidation of the theme as an important field of scientific research.